2014
DOI: 10.1116/1.4867170
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolatile memory devices with AlOx embedded Zr-doped HfO2 high-k gate dielectric stack

Abstract: Articles you may be interested inImproved thermal stability and electrical properties of atomic layer deposited HfO2/AlN high-k gate dielectric stacks on GaAs J. Vac. Sci. Technol. A 33, 01A136 (2015); 10.1116/1.4903367 Memory functions of nanocrystalline cadmium selenide embedded ZrHfO high-k dielectric stack J. Appl. Phys. 115, 084113 (2014); 10.1063/1.4867215Band offsets of metal-oxide-semiconductor capacitor with HfLaTaO/HfSiO stacked high-k dielectric Nanocrystalline ruthenium oxide embedded zirconium-dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…The magnitude of the V BD of the N 2 PDA sample is smaller than that of the O 2 PDA sample, i.e., −5.65 V vs. −6.1 V, which may be contributed by the difference in their physical thicknesses. 13,20 Also, the breakdown strength of the ZrHfO stack is related to the defect density in the original film. 19,26 Since the O 2 PDA sample has fewer defects in the ZrHfO bulk and HfSiO x interface layers than the N 2 PDA sample has, the former is more difficult to break down to form conductive paths than the latter is.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The magnitude of the V BD of the N 2 PDA sample is smaller than that of the O 2 PDA sample, i.e., −5.65 V vs. −6.1 V, which may be contributed by the difference in their physical thicknesses. 13,20 Also, the breakdown strength of the ZrHfO stack is related to the defect density in the original film. 19,26 Since the O 2 PDA sample has fewer defects in the ZrHfO bulk and HfSiO x interface layers than the N 2 PDA sample has, the former is more difficult to break down to form conductive paths than the latter is.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the 28 Si 16 O + component must be from the HfSiO x interface layer formed between the bulk ZrHfO and the Si substrate. 18,20 The above elements are good references for the comparison of the O 2 and N 2 PDA samples. The peak ratio of 28 Si 16 O + in the interface layer to 28 Si + in the Si substrate of the O 2 PDA sample is larger than that of the N 2 PDA sample, i.e., 2.21 vs. 1.59.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Much research has been focused on obtaining a high dielectric constant by stabilizing the tetragonal structure ZrO 2 or HfO 2 by doping, e.g., Si doping of HfO 2 , Er doping of HfO 2 , and Y doping of ZrO 2 , and Park et al reported remarkable enhancement of dielectric constant (∼47) by Al doping in relatively thick HfO 2 film . Although, there are some previous reports on undoped or nanocrystal embedded Zr–Hf-mixed oxides for gate dielectric, the research about combinations of Zr and Hf oxides in ternary metal oxide systems, which include matrices of ZrHf-mixed oxide and stabilizer dopant, for DRAM capacitor have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, various efforts are presented with metal nanocrystals such as Ni [17], Ir [18], Pt [19] and Au [20] with HfO2 films which improved the retention characteristics. Currently, Lu [21], Al [22], Zr [23] etc., dopants have been incorporated with HfO 2 but the formation of oxygen-related defect states, better switching and controlling dopant concentration for better NVM devices are still challenging. Therefore, Gadolinium (Gd) doped HfO 2 nanoparticles are fabricated by using a physical vapour deposition process to mitigate this issue and increase oxygen defect-related traps and provide better endurance in the device [24].…”
Section: Introductionmentioning
confidence: 99%